Thermal and mechanical properties of PLA/BN/BR ternary composite films - Baethu A. (2017)
© 2016 Trans Tech Publications. In this research, the effects of boron nitride (BN) and polybutadiene (BR) on thermal and mechanical properties of polylactic acid (PLA) composite films were studied. PLA thin film in the thickness of less than 0.2 mm was fabricated using the solvent casting method. The loadings of BN and BR of 0-7 wt% were applied to the PLA matrix. The morphologies of composite films were characterized by scanning electron microscopy (SEM). The thermal and mechanical properties were also investigated. It was found that the addition of BN and BR can improve the thermal properties of PLA composite films. PLA/BN3%/BR5% ternary composite films provided the higher thermal properties, tensile strength and Young's modulus, compared to PLA/BN1%/BR5% ternary composite films.